Evaluation of cell biological criteria for predicting the radiosensitivity of tumor cell lines to photon and neutron irradiation - Theron, C. S (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.M.S. (Medical Biochemistry)) -- University of Stellenbosch, 1995.